Revealing distinguishing factors between Space and Place in urban design literature - Abusaada, Hisham; Elshater, Abeer (Journal of urban design, 2021)
This article reviewed the normative distinguishing factors of 'space' and 'place' when associated with particular descriptions. A content analysis of 23 books revealed several distinguishing factors, and a systematic review of the SciVal and SCImago databases identified nine relevant journals. A scoping review of 26 articles in these journals found three disciplines that distinguished 'place' from 'space'; however, when there were descriptive words before either of them, the distinguishing factors were equivocal. The article argues that a focused effort on urban studies is required, and urban toolkits are relevant resources in that effort.